Comparison Between Broadband and Personal Exposimeter Measurements for EMF Exposure Map Development Using Evolutionary Programming - Alberto Nájera; Rocío Sánchez-Montero; Jesús González-Rubio; Jorge Guillén-Pina; Ricardo Chocano-del-Cerro; Pablo-Luis López-Espí (Applied Sciences)
In this study, we provide a comparison of radiofrequency electromagnetic field exposure level maps as determined using two approaches: a broadband meter (NARDA EMR-300) equipped with an isotropic probe in the range of 100 kHz to 3 GHz, and a Personal Exposimeter (Satimo EME Spy 140) in the range of 88 MHz to 5.8 GHz. The aim of this research was to determine the necessary adjustments to the measurements made with personal exposimeters to obtain RF-EMF exposure maps equivalent to those made with broadband meters. We evaluated different possibilities to obtain the best equivalence of measurements between both devices. For this purpose, the datasets obtained in both cases were analyzed, as well as the possible correction factors. First, the possibility of establishing a single or double correction factor depending on the existence (or lack thereof) of a line of sight with respect to the base stations was analyzed by minimizing the average value of the error between the values of the broadband meter and the corrected values of the personal exposure meter. Due to the differences observed in the exposure maps, a second procedure was carried out, in which a genetic algorithm was used to determine the ratio between the measurements from both methods (the broadband meter and personal exposure meter), depending on the existence (or lack thereof) of a line of sight, and we compared the exposure maps generated using kriging interpolation.